Nanometer-Scale Drug Synthesis: Innovations in Pharmaceutical Nanotechnology - Fajriyah, Maulida; Nurjannah, Neng Rita; Ambardhani, Nurul; Jannah, Nanda Raudhatil (Global Writing Academica Researching and Publishing, 2024)
Nanometer-scale drug development represents a new era in pharmaceutical technology, promising significant improvements in the efficacy and safety of treatments. Nanotechnology innovations in drug synthesis offer the potential to address existing global health challenges, including drug resistance and difficult-to-treat chronic diseases. However, the synthesis process at the nanometer scale faces significant obstacles, including biocompatibility issues, unclear regulations, and technical challenges in production. This research aims to explore and identify strategies to overcome these challenges, as well as assess the potential of nanotechnology innovation in the development of new drugs. The research method used is a descriptive qualitative approach, with data sourced from relevant previous literature. The data collected is then processed to gain an in-depth understanding of the research subject. The conclusions of this study indicate that although the challenges in nanometer-scale drug synthesis are significant, the potential for nanotechnology innovation in pharmaceuticals is revolutionary. Effective strategies to overcome these challenges include the development of new synthesis methods, advances in characterization techniques, and close interdisciplinary collaboration. Policies and regulations that support innovation are urgently needed to facilitate the development and implementation of these new medicines. Finally, the future of nanometer-scale medicine depends on increasing access and desirability, taking into account ethics and safety in product development.